1,4-Bis(4-tert-butylbenzyl)piperazine - Luo, Li-Juan (International Union of Crystallography, 2011)
The complete molecule of the title compound, C(26)H(38)N(2), is generated by a crystallographic inversion centre. The piperazine ring adopts a chair conformation with pseudo-equatorial substituents. In the crystal, molecules interact only by van der Waals forces.